Subject and Tasks of Biophysics (Texas Journal of Agriculture and Biological Sciences, 2023)
The article deals with the formation of basic competencies when teaching a biophysics course. The types, functions, pedagogical and psychological qualities of the basic competencies on which they are based are substantiated